Cross Sectional study to evaluate Psychosocial impact of Covid 19 among medical students of BMCTH - Guragain, Parth; Niraula, Aarju; Kafle, Tara Kumari; Bhagat, Baby Kumari; Agarwal, Hulas (Birat Journal of Health Sciences, 2023)
Introduction: COVID-19, a profoundly contagious viral disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has had a devastating impact globally, leading to over 6 million fatalities worldwide. Covid 19 caused isolation, anxiety, grief, economic stress, and disrupted routines, leading to mental struggles, strained relationships, and increased demand for mental health services globally. Objectives: The objectives of this study were to find out psychosocial impact of covid 19 among medical students of BMCTH and to assess the factors associated with psychosocial impact of covid 19. Methodology: A cross-sectional study was carried out among all medical students of Birat medical college teaching hospital from August, 2022 to January 2023. Data was collected from 258 eligible participants using GHQ12 questionnaire. Chi-square test was applied for assessing association between dependent and independent variables and binary logistic regression analysis was used to find the determinants. Results: Present study was conducted among 258 medical students. Among them 43.0% had normal psychological status, 27.5% were in borderline 15.5% showed evidence of psychological distress and 14.0% were experiencing severe psychological distress. Bivariate analysis between socio-demographic characteristics and psychosocial status showed gender, work overload, work hours in covid ward, exposure to false covid information and covid quarantine were significantly associated with psychological distress at p- value < 0.05. Further important variables were run for multivariate analysis which revealed age (B=3.46, CI:1.45-8.23 and P=0.005), gender (B=3.20, CI: 1.61-6.37 and P=0.001) and work overload (B=9.63, CI: 4.32-21.49 and P=0.000) were found as significant predictors/determinants of psychological distress. Age greater than 24 years, female gender and higher work load were significantly associated with psychological distress. Conclusion: The psychological distress among the medical students due to covid 19 was in appalling situation. The study found age >24 years, female gender and higher workload were the predictor of the psychological distress Integrated efforts from medical college, parents, peers and faculties are to be initiated to address the existing problems.